Mortal secrets : truth and lies in the age of AIDS - Klitzman, Robert (UPCC book collections on Project MUSE., 2003)
Annotation In the era of the Internet and Oprah, in which formerly taboo information is readily available or freely confided, secrecy and privacy have in many ways given way to an onslaught of confession. Yet for those who are HIV positive, decisions about disclosure of their diagnosis force them to confront intimate, fundamental, and rarely discussed questions about truth, lies, sex, and trust. Drawing from interviews with over seventy gay men and women, intravenous drug users, sex workers, bisexual men, and heterosexual men and women, the authors provide a detailed portrait of moral, social, and psychological decision making. The interviews convey the complex emotions of love, lust, longing, hope, despair, and fear that shape individual dilemmas about whether to disclose to, deceive, or trust others concerning this disease. Some of those interviewed revealed their diagnosis widely; others told no one. Some struggled and ultimately told their partners; others spoke in codes or half-truths. One woman discovered her husband's diagnosis in a diary; when confronted, he denied it. Each year in the United States, 40,000 new cases of HIV arise, yet approximately one-third of the 900,000 Americans who are infected do not know it. As treatments have improved, unsafe sexual behavior has increased and efforts at prevention have stalled. Many of those infected continue to fear and experience rejection and discrimination. Addressing broad debates about the nature of secrecy, morality, and silence, this book explores public policy questions in the light of the nuanced, private decisions that are shaping the course of an epidemic and have broader indications for all.